The Development of Comparative Grammatical Material between the Two Doctrines of Kufa and Basra/تطوير المادة النّحوية المقارنة بين مذهبي الكوفة والبصرة - jamidi jamidi (Jurnal Al-Maqoyis, 2021)
The aims of this research are: 1) to reveal the different elements of Nahwu between Basrah and Kufa. 2) Develop Nahwu teaching materials based on the differences between the two schools of thought. 3) Measuring the effectiveness of implementation of developed teaching materials.‎ This research uses research and development type. This study started with Borg and Gall's adaptation model with the steps; needs analysis process, initial product development, expert validation and its revisions, small and large group trials. The researcher conducted a pretest and posttest which was analyzed using the T test formula. The results of this study are: 1) Differences of opinion about Nahwu between Bashrah and Kufa are found in words, terms and sentence structure comments. 2) Teaching materials were developed based on needs analysis, expert validation which was tested in small groups and large groups with three major themes, namely the first chapter of differences in tarkib, second differences in ‎I'rab, third differences in 'amil with deductive approach and with bahasapatterns of language effectiveness about Nahwu rules. 3) The results of the T test using SPSS 24 showed that the teaching materials developed were "very effective in learning Nahwu based on the differences between Basrah and Kufah."